Circular Economy and Rebound Effects: Exploring The Gaps Between Principles and Practice - Paweł BARTOSZCZUK (Communications of International Proceedings, 2022)
Three basic categories of industrial economy are distinguished by the scholars: linear, circular and performance. Linear economy flows like a river, turning natural resources into base materials and products for sale through a series of value-adding steps. At the point of sale, ownership and liability for risks and waste pass to the buyer (who is now owner and user). This paper particularly argues that brands must integrate circularity’s across supply chains, rather than limiting them to the waste stage. The analysis explores the gaps between circular economy principles and practice, identifying challenges inherent in a few good practices. The benefits of the circular economy are often taken for granted. Nevertheless, some premises to believe that rebound effects may counteract such benefits by increasing overall consumption or “growing the pie.” It concludes with recommendations for further study of the circular economy.
Keywords: 3R; Circural economy; backfire; benefits; industrial economy rebound effects sustainable development.